Vocabulary Notebookand Young Learners' Vocabulary Mastery - Efendi, Lusy Nur (2014)
This study is centered on the issue of keeping vocabulary notebook in increasing young learners' vocabulary mastery. It is aimed at discovering whether or not keeping vocabulary notebook is effective in increasing young learners' vocabulary mastery and how the response of young learners toward keeping vocabulary notebook is. A quasi-experimental design was used in this study. The data were collected through vocabulary pre-test and post-test to gain relevant data in terms of the effectiveness of keeping vocabulary notebook. Moreover, questionnaire was used to investigate students' response toward keeping vocabulary notebook for then being analyzed quantitatively. The study involved 50 participants of fifth grade students of an elementary school in Majalengka that were divided into control and experimental group. Experimental group received the treatment of keeping vocabulary notebook, while control learned vocabulary by using conventionallearning method where the students wrote down the vocabulary in their usual notebook. The study was conducted in six week meetings that consist of four week meetings of treatment and two week meetings of pre-test and post-test. Then, close-ended questionnaire was given to the participants in experimental group only. The findings revealed that keeping vocabulary notebook was effective in increasing young learners' vocabulary mastery. It was indicated by the means computation in which the means of control and experimental group before receiving the treatments were (M=46.08) and (M=43.44) while the means of control and experimental group after receiving the treatments were (M=71.52) and (M=86.00). Moreover, the result of independent t-test computation of post-test score of control and experimental group showed significant difference in which that the tobt(-4.196) is higher than the tcrit(1.677) at the level of significance 0.05. Furthermore, keeping vocabulary notebook has a high effect to young learners in learning English vocabulary was justified by the computation of effect size (0.518). In addition, young learners' showed some positive responses and opinions about keeping vocabulary notebook. Based on the findings, it is expected that keeping vocabulary notebook can be applied in young learners' activity to master vocabulary inside or outside classroom. Even though, vocabulary notebook can be used as autonomy learning, keeping vocabulary notebook will gain optimal result, if the teachers guide the students by giving them feedback actively. In other words, keeping vocabulary notebook has a significant influence in increasing young learners' vocabulary. For that reason, this kind of method is recommended to be applied on teaching vocabulary to young learners. Penelitianiniberkaitandenganisumembuatcatatankosa kata atauvocabulary notebook untukmeningkatkanpenguasaankosa kata anak-anak.Tujuandaripenelitianiniadalahuntukmengetahuiefektifitaspenggunaanvocabulary notebook dalammeningkatkanpenguasaankosa kata anak-anakdanseperti aparesponmerekaterhadappenggunaanvocabulary notebook tersebut. Eksperimensemumerupakandesaindaripenelitianini. Data penelitian yang relevandikumpulkanmelaluipre-test, post-test, dankuesioner.Terdapat 50 respondenpenelitian yang diambildarisiswakelas 5 di salahsatuSekolahDasar di Majalengka. Merekadibagikedalamkelompok control dankelompokeksperimen. Kelompok eksperimen diberikan treatment belajar kosa kata bahasa Inggris dengan Vocabulary notebook, sementara kelompok kontrol tidak diberikan tratment seperti kelompok eksperimen, melainkan belajar kosa kata bahasa Inggris dengan metode konvensional. Penelitian ini berlangsung selama 6 minggu, dimana 4 minggu diperuntukkan untuk melakukan treatment dan 2 minggu untuk pre-test dan post-test. Setelahitu, kuesionerdibagikankepadasiswa di kelompokeksperimen.Data yang diperolehdianalisissecarakuantitatif.HasildariperhitungantersebutmembuktikanbahwaVocabulary Notebook terbuktiefektifdalammeningkatkanpenguasaankota kata anak-anak. Hal tersebutterlihatdariperbedaan nilai rata-rata dari kelompok kontrol dan eksperimen pada saat sebelum diberikan treament sebesar (M=46.08) dan (M=43.44), sedangkan nilai rata-rata dari kelompok kontrol setelah diberikan treament adalah (M=71.52) and (M=86.00). Selain itu, hasil perhitungan independent t-test menunjukkan perbedaan nilai post-test yang signifikan dari kelompok kontrol dan eksperimen dimana nilai tobt(-4.196) lebih besar dari tcrit(1.677) pada tingkat segnifikan 0.05. selain itu, penggunaan vocabulary notebook mempunyai efek yang besar dalam pembelajaran kosa kata bahasa Inggris pada anak-anak. Hal terseebut terbukti dari hasil perhitungan effect size sebesar (0.518).Selainitu, hasildarikuesioner pun menunjukanbahwaanak-anakmeresponpenggunaanvocabulary notebook secarepositif.Makadariitu, Vocabulary notebook sangatdianjurkanuntukdigunakansebagaikegiatanpelengkap di dalamkelasmaupun di luarkelasuntukbelajarkosa kata bahasaInggris. Meskipun vocabulary notebookbisa digunakan untuk pembelahjaran mandiri, penggunaanya akan lebih optimal jika diawasi dan diberi masukkan oleh guru. Dengan kata lain, pembelajaran kosa kata dengan menggunakan vocabulary notebooksangat dianjurkan.